Single‐Molecule Detection: Single‐Molecule Electrical Detection with Real‐Time Label‐Free Capability and Ultrasensitivity (Small Methods 5/2017). Issue 5 (May 2017) - Gu, Chunhui; Jia, Chuancheng; Guo, Xuefeng
Abstract : Xuefeng Guo and co‐workers discuss the approach of single‐molecule electrical detection in article number1700071 . This has the potential of being a mainstream methodology capable of studying single‐molecule/single‐event dynamics in an interdisciplinary realm. This is because it provides a reliable and promising platform to probe detailed information of either chemical reactions or biological activities usually hidden in ensemble‐averaged experiments, which is of crucial importance to chemical, biological, and medical sciences.